Digitalisasi UMKM: Pemberdayaan Pelaku Usaha Mikro, Kecil, dan Menengah melalui Platform E-Commerce dan Google Maps - Indah Muliati; Ananta Rinaldi; Jefri Al Hafis; Mutiara Fadilah Rahmadhani; Rahma Fitri Annisa (CV. ITTC INDONESIA, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy; however, most still operate conventionally and have not optimally utilized digital technology. This Community Service Program (KKN) aims to improve the digital literacy and skills of MSME actors through a one-day socialization and training program in Nagari Sirukam. The activities included an introduction to digital marketplaces, hands-on training in creating seller accounts and uploading products on Shopee, and registering business locations on Google Maps. The method applied was direct demonstration (hands-on training) with individual assistance supported by visual media. The results showed an improvement in participants’ understanding and digital skills, the establishment of active online store accounts, and the successful digital registration of business locations. This program proved effective in accelerating technology adoption among local MSMEs. This activity contributes to the achievement of SDGs point 8 (Decent Work and Economic Growth) and point 9 (Industry, Innovation, and Infrastructure).